Comment on: Toward an optimal contraception dosing strategy. - Giuseppe Benagiano; Andrea R Genazzani; Giovanni Grandi; Sun-Wei Guo; Marwan Habiba (PLoS Computational Biology)
The optimal contraception dosing strategy proposed by Gavina et al. recently is a commendable attempt to model a complex physiological process with potenial to apply to real-life data. However, there is a need to take into account the real challenges that arise when moving from the theory to its practical application, and it is important that lessons learnt from clinical studies be taken into consideration in any theoretical modelling. In this manuscript, we spell out these lessons and elaborate practical challenges facing their model.